Social Dominance Orientation, Dispositional Empathy, and Need for Cognitive Closure Moderate the Impact of Empathy-Skills Training, but Not Patient Contact, on Medical Students' Negative Attitudes toward Higher-Weight Patients - Meadows, Angela; Higgs, Suzanne; Burke, Sara E.; Dovidio, John F.; van Ryn, Michelle; Phelan, Sean M. (Frontiers in Psychology, 2017)
Anti-fat bias in healthcare providers and medical students has serious implications for quality of care of higher-weight patients. Studies of interventions aimed at reducing anti-fat attitudes in medical students have generally been disappointing, with little enduring effect. It is possible that some students may be more receptive to prejudice-reducing influences than others, due to underlying differences in their personal characteristics. It is also possible that attitudes toward patients, specifically, may differ from anti-fat attitudes in general, and prejudice-reduction effectiveness on patient-specific attitudes has not yet been evaluated. The present study explored the effect on general and patient-specific anti-fat attitudes of (1) contact with higher-weight individuals prior to and during medical school; and (2) training designed to increase medical students’ empathy toward patients by encouraging them to take the patient’s perspective during clinical encounters. The moderating role of individual difference factors on effectiveness of contact and student-reported hours of empathy training on patient-specific attitudes was assessed. A total of 3,576 students enrolled across 49 US medical schools completed an online survey at the start of their first year of medical school and at the end of their fourth year. Favorable contact experience with higher-weight patients predicted improved attitudes toward obese patients after four years of medical school, and appeared sufficient to partially offset the effects of dislike of higher-weight individuals at baseline. The impact of favorable contact on general anti-fat attitudes was less strong, highlighting the importance of using target-specific outcome measures. The positive effects of favorable contact on attitudes toward higher-weight patients did not differ based on students’ baseline levels of social dominance orientation, dispositional empathy, or need for cognitive closure. In contrast, the effectiveness of training did vary by student characteristics, generally being more effective in students who were more egalitarian and empathic at baseline, with little effect, or even adverse effects in students low in these traits. Overall, however, perspective-taking training produced only small improvements in attitudes toward higher-weight patients.